2015
DOI: 10.4028/www.scientific.net/amm.754-755.990
|View full text |Cite
|
Sign up to set email alerts
|

Waste to Wealth for the Edible Bird Nest Industry

Abstract: Edible bird nest (EBN) is a product obtained from the salivary excretion of different species of swiftlets during the breeding season. It is an expensive health food product. The raw EBN needs intensive cleaning before it can be consumed. Currently, EBN is increasingly used in cosmetic products. The cleaning procedure generally produced about 30 % (w/w) of waste. To date, there is no work conducted to study the composition of the waste recovered from the cleaning process and converting the waste into useful do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
3
7
0
Order By: Relevance
“…Visually, the FTIR spectrums of all EBN samples displayed similar patterns. Similar patterns of absorption spectrum with the current study was also reported by Guo et al 34 and Hamzah et al, 35 indicating the high purity of all the samples. Table 2 shows the absorption peaks that are present in the EBN samples with the corresponding functional groups as indicated in Fig.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopy Analysissupporting
confidence: 92%
See 4 more Smart Citations
“…Visually, the FTIR spectrums of all EBN samples displayed similar patterns. Similar patterns of absorption spectrum with the current study was also reported by Guo et al 34 and Hamzah et al, 35 indicating the high purity of all the samples. Table 2 shows the absorption peaks that are present in the EBN samples with the corresponding functional groups as indicated in Fig.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopy Analysissupporting
confidence: 92%
“…Furthermore, symmetric bending vibration of carboxylic group (COOH) with wavenumber from 1438.75 to 1439.68 cm −1 was detected, similar to Hamzah et al 35 in EBN samples. Meanwhile, all samples showed a peak close to 1400.0 cm −1 which indicates the presence of polysaccharides, such as the bending vibration of the C H (CH 2 ) group.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopy Analysissupporting
confidence: 82%
See 3 more Smart Citations